Fabricating an optimal rutile TiO2 electron transport layer by delicately tuning TiCl4 precursor solution for high performance perovskite solar cells. (February 2020) - Lu, Hao; Zhong, Junyu; Ji, Chen; Zhao, Junting; Li, Dong; Zhao, Run; Jiang, Yucheng; Fang, Song; Liang, Taotao; Li, Huishu; Li, Chang Ming
Abstract: Herein, we construct electron transport layers (ETLs) with a TiO2 film containing rationally quantity-adjusted short TiO2 nanowire arrays and nanoflowers composite by delicately tuning TiCl4 precursor solution for high-performance perovskite solar cells. The optimal as-prepared TiO2 short-nanowire arrays/nanoflowers composite ETL-based device can deliver a high power conversion efficiency (PCE) of more than 20%, which ranks the highest among all single rutile type TiO2 ETL-based perovskite solar cells up to date. Systematic mechanism investigation discovers that 1-D TiO2 short-nanowire arrays combined with quantitatively tailored nanoflowers as a refection umbrella can offer short direct charge transport pathways, low leakage current, low charge transfer resistance and low recombination rate as well as improved light harvest from efficient light scattering. This work sheds a light on designing an efficient electron transport layer by rationally tuning a precursor solution while offering a facile approach to fabricate an inexpensive nanostructure for electron transport layers toward high-performance perovskite solar cells. Graphical abstract: Image 1 Highlights: Multiple morphologies of rutile TiO2 were prepared by same TiCl4 solution. Planar and mesoporous perovskite solar cells are compared within same system. TiO2 nanowire increase charge transport ability and thicken perovskite layer. TiO2 nanoflowers do a good light reflection ability in perovskite solar cell.